No germline mutations in supposed tumour suppressor genes SAFB1 and SAFB2 in familial breast cancer with linkage to 19p - Svensson Jan H; Mattsson Jan; Yhr Maria; Behboudi Afrouz; Abel Frida; Bergman Annika; Karlsson Per; Nordling Margareta (BMC, 2008)
Abstract Background The scaffold attachment factor B1 and B2 genes, SAFB1/SAFB2 (both located on chromosome 19p13.3) have recently been suggested as tumour suppressor genes involved in breast cancer development. The assumption was based on functional properties of the two genes and loss of heterozygosity of intragenic markers in breast tumours further strengthened the postulated hypothesis. In addition, linkage studies in Swedish breast cancer families also indicate the presence of a susceptibility gene for breast cancer at the 19p locus. Somatic mutations in SAFB1/SAFB2 have been detected in breast tumours, but to our knowledge no studies on germline mutations have been reported. In this study we investigated the possible involvement of SAFB1/SAFB2 on familiar breast cancer by inherited mutations in either of the two genes. Results Mutation analysis in families showing linkage to the SAFB1/2 locus was performed by DNA sequencing. The complete coding sequence of the two genes SAFB1 and SAFB2 was analyzed in germline DNA from 31 affected women. No missense or frameshift mutations were detected. One polymorphism was found in SAFB1 and eight polymorphisms were detected in SAFB2. MLPA-anlysis showed that both alleles of the two genes were preserved which excludes gene inactivation by large deletions. Conclusion SAFB1 and SAFB2 are not likely to be causative of the hereditary breast cancer syndrome in west Swedish breast cancer families.